Monitoring indicators for municipal land management plan. Case of study: Rivadavia, Mendoza, Argentina: Article - Berón, Nélida; Cuello Rüttler, Lucia; Santoni, Luciano (Geographicalia, 2023)
The Institute CIFOT has elaborate the Municipal Land Management Plan of Rivadavia, Mendoza, Argentina, together with the municipal technical team. This plan was developed between 2019 and 2022 and finally approved in May 2022 by Municipal Ordinance. The aim of this study is to present, on the one hand, the methodology with which the Municipal Plan was elaborated and, on the other hand, to propose a new one for the construction of indicators that could measure the annual progress in the programs and projects proposed in the PMOT at the time of applying the annual Internal Audit
Keywords: Municipal Plan; Land Management; Indicators; Internal Audit